Business Strategy Analyis And Recomendation For Popkeys (The Indonesian Journal of Business Administration, 2015)
Abstract - Popkeys as one of the SMEs that aware of the opportunity that has given by internet, emerge among the Indonesian society to introduce a brand new product for the society which is a keycaps or key cover. Popkeys facing several issues for their business and one of their main issues is the sales that keep declining after the first month of sales. External analysis such as Porterâ€™s Five Forces and Macro-environment analysis also internal analysis such as Value Chain analysis, SWOT analysis, EFAS and IFAS, Marketing mix, and any other tools are conducted. Survey for the awareness of the keycaps product and Popkeys brand are also conducted in this final project. The result of the analysis is that there are three main root causes that will be the main focus on this research: lack of brand and product awareness, not effective marketing strategy, and operational/production process that Popkeys has a very high dependency on China vendor that will affect the sales of their product. To increase the awareness of their keycaps product and their Popkeys brand, Popkeys needs to do the Integrated Marketing Communication program (advertising, endorsement, joining events and bazaars, and any other IMC tools) and also determine a more clearly STP. As for the production/operational side, Popkeys need to loosen or even better release their dependency on China vendor by looking a new local vendor in Indonesia. Action plan and implementation plan are also conducted for Popkeys from November 2014 until November 2015. In the action plan and implementation plan will be discussed a more specific time for each Popkeys action plan.Keywords: keycaps, internet, business strategy, brand awareness, SME, social mediaÂ